Academic Engagement in Health Sciences students at the University of Málaga (Spain): four years follow up - Moreno-Morales, Noelia; Labajos-Manzanares, María Teresa; Casuso Holgado, María Jesús (My University, 2014)
Introduction. Student engagement in post-school education has been researched since the 1990s, have been considered as an important factor in determining student learning and personal development during college [1,2]. The concept of engagement in relation to the student university experience is generally acknowledged as a multidimensional phenomenon that may result from a variety of factors relating to the individual and the context in which they are learning [3]. Objectives. To know and compare the levels of engagement at university in Health Sciencies students (Nursing, Physiotherapy, Podiatry and Occupational Therapy) along the first, second and last year of their degree. Relevance. Educational institutions play an important role in encouraging student engagement. It is necessary to know how students are engaged with their studies at university. Participants. The sample consisted of 250 freshman students (28% of the total population) at the University of Málaga (Spain) who were followed-up from 2009 to 2012. Methodology. Descriptive longitudinal study. Students were asked to fill out an on-line questionnaire (UWES-S) in May 2010, 2011 and 2013. Mean and standard deviation were calculated for each engagement dimension (vigor, dedication and absorption). Anova test was used for mean comparisons. Results. Although it has been observed a slight decrease in the levels of engagement from the first year of degree, differences were no statistically significant. In general, it can be say that these students feel engaged at university along their degree. Mean scores for engagement dimensions range from 4.89 to 2.9 into a Likert scale of 6 points. 2009-10 2010-11 2012-13 Dimensions Mean SD Mean SD Mean SD Vigor 3,13 1,02 2,90 1,04 3,00 1,09 Dedication 4,89 1,07 4,64 1,32 4,74 1,32 Absorption 3,15 1,28 2,93 1,23 3,15 1,32 Conclusions. In a general way, it can be said that the Health Sciencies students analyzed are engaged at university and show a high dedication to their degree. However, it is also important to highlight that engagement scores don´t rise in the last year as it would be expected taking in account that in this year students reach the most practical knowledge and start their profession in the society. Keywords: academic engagement, university, health sciences. References 1. Astin AW: What matters in college: four critical years revisited. San Francisco, CA: Jossey-Bass; 1993. 2. Pascarella ET, Terenzini PT: How collage affects students. A third decade of research, Volume 2. San Francisco, CA: Jossey-Bass; 2005. 3. Fredericks JA, Blumenfeld PC, Paris AH: School engagement: potential of the concept, state of the evidence. Rev Educ Res 2004, 74:59–109.
Keywords: Biomedicina - Estudio y enseñanza; Education; Healh Sciences; Engagement